Analysis of static electricity generation and elimination in the process of food powder screw feeding. (8th August 2022) - Shen, Changpu; Li, Yongxiang; Wang, Yi; Xu, Xuemeng
Abstract: The static electricity in the powder can easily cause poor packaging accuracy, incomplete heat‐sealing of the packaging bag and certain safety hazards. Therefore, the electrostatic generation and elimination of wheat flour and wheat starch were studied in the process of powder screw feeding. Firstly, taking powder particle size, screw speed and conveying distance as influencing factors, the law of static electricity generation in the process of powder screw conveying is studied. Then, an adjustable DC power supply and an ion fan were used to apply voltage and ion wind during the powder screw feeding process to study the elimination of powder static electricity. The research results show that the electrostatic charge of wheat flour and wheat starch is positive. The greater the screw speed, the more severe the powder collision and friction, and the greater the increase in powder charge‐to‐mass ratio. The larger the conveying distance, the greater the increase in the powder‐to‐mass ratio, and when the conveying distance reaches 5200 mm, the experimental powder‐to‐mass ratio tends to be stable. The gain and loss of the charge of wheat starch with small particle size is obviously greater than that of wheat flour with large particle size. The ability and stability of adding ion wind at the outlet of the screw feeder to eliminate static electricity are obviously stronger than the ability and stability of adding voltage to eliminate static electricity. Practical applications: The static electricity generated in the process of screw conveying and feeding causes trouble to the packaging weighing, packaging sealing and safety production of powder. Therefore, this paper studies the electric characteristics of food powder in the process of screw transportation and the influence of various factors on the electrostatic generation law, and also through experiments to compare the two methods of electrostatic elimination. This study provides ideas and references for reducing the generation and elimination of static electricity in the process of screw transportation of food powder, so as to improve the packaging accuracy, packaging quality and reduce safety risks in actual industrial production. Abstract :